Experimental performance of compact UWB antenna for breast cancer screening - Padhi, S; Mase, A; Ito, N; Zhang, Dan (IEEE, 2012)
This paper presents experimental performances of the algorithm used for detection of malignant tissue in breast. The algorithm uses ultra-short pulse radar (USPR) technique along with confocal microwave imaging (CMI) algorithm based on synthetic aperture radar (SAR) to detect tumor cells or tissue. A compact Vivaldi antenna having ultra-wideband (UWB) performance with bandwidth 3 GHz to 8 GHz is used as transceiver and an impulse with no distortion is used as an excitation signal in our experiment. We used various synthetic breast phantom and metallic or high-k dielectric balls as tumor. The skin subtraction method using Teflon cover seems to be promising for this experiment.